A New Estimate of North American Mountain Snow Accumulation From Regional Climate Model Simulations. Issue 3 (10th February 2018) - Wrzesien, Melissa L.; Durand, Michael T.; Pavelsky, Tamlin M.; Kapnick, Sarah B.; Zhang, Yu; Guo, Junyi; Shum, C. K.
Abstract: Despite the importance of mountain snowpack to understanding the water and energy cycles in North America's montane regions, no reliable mountain snow climatology exists for the entire continent. We present a new estimate of mountain snow water equivalent (SWE) for North America from regional climate model simulations. Climatological peak SWE in North America mountains is 1, 006 km 3, 2.94 times larger than previous estimates from reanalyses. By combining this mountain SWE value with the best available global product in nonmountain areas, we estimate peak North America SWE of 1, 684 km 3, 55% greater than previous estimates. In our simulations, the date of maximum SWE varies widely by mountain range, from early March to mid‐April. Though mountains comprise 24% of the continent's land area, we estimate that they contain 60% of North American SWE. This new estimate is a suitable benchmark for continental‐ and global‐scale water and energy budget studies. Key Points: A new technique for estimating average snow water storage is presented for North American mountains Comparisons suggest that current global model estimates underestimate mountain snow by >50% Mountains hold a disproportionate amount of snow water storage, highlighting the need for better mountain representation in modeling